Philosophy of Pacu Jalur: Sustainable of Character Development in Pacu Jalur Values on the Pancasila Student Profile - Suroyo Suroyo; Bima Maulana Putra; Bedriati Ibrahim; Antonia Soriente (Kementerian Koordinator Bidang Pembangunan Manusia dan Kebudayaan Republik Indonesia, 2023)
Pacu Jalur is a rowing competition which is held every year in Kuantan Singing District, Riau Province. The values contained in the runway have a picture that can become the prevailing values in society. This research is descriptive qualitative research with interview technique as the research data instrument, besides that observation and documentation are also conducted to support the data collected by interview technique. The population of this research is the people who take part in the track race, while the key informants of this study are the participants of the spur-of-the-road festival using purposive sampling as a sampling technique. The results show that the values of sustainable character development that are being promoted by the Ministry of Education and Culture regarding the profile of Pancasila students, where character education focuses more on the values listed in Pancasila, so that the values on the Pancasila student profile have the values contained in the philosophical values. contained in the track race. This is also because the Pacu Jalur has adopted the values of the ancestors that contain social meaning and high integrity, so that the philosophical values in Pacu Jalur have a similar meaning to the profile of Pancasila students.